Genome-Wide Dna Methylation Analysis of Hippocampal Tissue in a Murine Model of Attention Deficit-Hyperactivity Disorder - Ugarte-Martinez, G; Morales-Munoz, B; Vidal-Soto, R; Constandil-Cordova, L; Rozas-Salas, C; Contreras-Pacheco, D; Godoy-Gajardo, F; Lopez, C (Public Library of Science, 2025)
Attention Deficit-Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder with a prevalence around 5% in children and adolescents and 2.5% in adults. Recent reports using GWAS approaches have identified several genetic risk loci for this disorder. However, the epigenetic influence of extrinsic factors during pregnancy or the exposure to environmental factors during childhood, on the onset of the disorder remains unclear. This question has been addressed by analyzing blood or saliva samples from ADHD patients or by postmortem analysis. The aim of this study was to determine differential patterns in DNA methylation in fresh hippocampal samples using a murine model of ADHD. We analyzed the genome-wide pattern of differentially methylated CpG sites using the Illumina Infinium Mouse Methylation BeadChip in fresh hippocampal samples from the prenatal nicotine exposure (PNE) mouse model of ADHD and control animals. Our analysis revealed 218 DMPs including genes associated with growth factors signaling, such as adhesion G protein-coupled receptor B2 (ADGRB2), leukemia inhibitory factor receptor (LIFR) and erb-b2 receptor tyrosine kinase 3 (ERBB3) involved in synaptogenesis, proliferation, and differentiation of neural stem cells. The functional gene enrichment analysis of differentially methylated positions (DMPs) revealed the nervous system development as the biological process with highest enrichment factor. In addition, the GO and KEEG enrichment analysis of 113 differentially methylated regions (DMR) revealed several loci associated with the positive regulation of Hippo signaling (involved in neuronal development) in PNE samples. In addition, our results revealed a DMP previously associated to ADHD patients supporting the PNE murine model of ADHD. These results are relevant in terms of the validation of PNE model of ADHD and for the identification of epigenetic markers of the disorder in humans. In addition, our results are relevant for the characterization of the cellular and molecular mechanisms underlying the ADHD, currently unknown. © 2025 Vidal et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.